Older Jobseekers’ Temporal Identity Work: Relating to Past, Present, and Future - Steel, Tytti; Tuori, Annamari (Nordic Journal of Working Life Studies, 2019)
This paper examines how older unemployed people cope with unemployment through temporal identity work. By temporal identity work, we refer to identity work that takes place at junctions between past, present, and future working lives and which relates to these tenses as a part of identity construction.The paper is based on 30 semi-structured interviews with jobseekers aged 50+ living in a region that has undergone deindustrialization and suffers from high unemployment rates. In the interview material, we identified three main types of identity work: Relying on the past, renewing oneself, and tweaking one’s working identity. This article identifies ‘respectably unemployed’ as the cultural construction in relation to which identity work is done in a society that values paid work highly. The paper contributes to the literature on age and unemployment by enhancing the understanding of older jobseekers’ identity work as a contextually embedded temporal process.